2022
DOI: 10.3390/ijerph192114504
|View full text |Cite
|
Sign up to set email alerts
|

On Serendipitous Campus Meetings: A User Survey

Abstract: With campuses opening up and stimulating interactions among different campus users more and more, we aim to identify the characteristics of successful meeting places (locations) on campus. These can help practitioners such as campus managers and directors to further optimize their campus to facilitate unplanned or serendipitous meetings between academic staff and companies. A survey on three Dutch campuses, including questions on both services and locations, was analyzed both spatially and statistically using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…In the focus groups the results from the survey and the previous study in which campus directors indicated the key success factors for unplanned meetings on campuses [31] were confirmed, and the understanding of why these findings occurred were deepened. This approach also yielded additional findings.…”
Section: A Comparison Of Findingsmentioning
confidence: 57%
See 4 more Smart Citations
“…In the focus groups the results from the survey and the previous study in which campus directors indicated the key success factors for unplanned meetings on campuses [31] were confirmed, and the understanding of why these findings occurred were deepened. This approach also yielded additional findings.…”
Section: A Comparison Of Findingsmentioning
confidence: 57%
“…The authors conducted a related survey of 443 academic staff members on three Dutch university campuses [31]. To ensure that interrelationships could be discussed and in-depth reasons could surface [32], a qualitative approach in the form of a focus group was chosen to better understand why respondents would choose one location over another.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations